Left Atrial Hypertension, Electrical Conduction Slowing, and Mechanical Dysfunction – The Pathophysiological Triad in Atrial Fibrillation-Associated Atrial Cardiomyopathy - Eichenlaub, Martin; Mueller-Edenborn, Bjoern; Minners, Jan; Jander, Nikolaus; Allgeier, Martin; Lehrmann, Heiko; Schoechlin, Simon; Allgeier, Juergen; Trenk, Dietmar; Neumann, Franz-Josef; Arentz, Thomas; Jadidi, Amir (Frontiers in Physiology, 2021)
Background: Atrial fibrillation (AF) is the most common arrhythmia and a significant burden for healthcare systems. Presence of relevant atrial cardiomyopathy (ACM) is related to persistent AF and increased arrhythmia recurrence rates after pulmonary vein isolation (PVI). Objective: To investigate the association of left atrial pressure (LAP), left atrial electrical (invasive atrial activation time (IAAT), amplified p-wave duration (aPWD)) and mechanical (left atrial emptying fraction (LA-EF), left atrial strain (LAS)) functional parameters with the extent of ACM and their impact on arrhythmia recurrence following PVI. Materials and Methods: Fifty patients (age 67(IQR:61-75)years, 78% male) undergoing their first PVI for persistent AF were prospectively included. LAP (maximum amplitude of the v-wave), digital 12-lead-electrocardiogram, echocardiography and high-density endocardial contact mapping were acquired in sinus rhythm prior to PVI. Arrhythmia recurrence was assessed using 72-hour Holter electrocardiogram at six and 12 months post PVI. Results: Relevant ACM was diagnosed in 25/50(50%) patients. Compared to patients without ACM, patients with ACM had higher LAP (17.6[10.6-19.5]mmHg versus 11.3[ 7.9-14.0]mmHg, p=0.009). The corresponding values for the electrical parameters were 166(149-181)ms versus 139(131-143)ms for IAAT(p<0.0001), 163(154-176)ms versus 148(136-152)ms for aPWD(p<0.0001), and for the mechanical parameters 27.0(17.5-37.0)% versus 41.0(35.0-45.0)% for LA-EF(p<0.0001) and 15.2(11.0-21.2)% versus 29.4(24.9-36.6)% for LAS during reservoir phase(p<0.0001). Furthermore, all parameters showed a linear correlation with ACM extent(p<0.05 for all). Receiver-operator-curve-analysis demonstrated a LAP≥12.4mmHg (AUC:0.717, sensitivity:72%, specificity:60%), a prolonged IAAT≥143ms (AUC:0.899, sensitivity:84%, specificity:80%), a prolonged aPWD≥153ms (AUC:0.860, sensitivity:80%, specificity:79%)), an impaired LA-EF≤33% (AUC:0.869, sensitivity:84%, specificity:72%), and an impaired LAS during reservoir phase≤23% (AUC:0.884, sensitivity:84%, specificity:84%)) as predictors for relevant ACM. Arrhythmia recurrence within 12 months post PVI was significantly increased in patients with relevant ACM, electrical dysfunction with prolonged IAAT≥143ms and mechanical dysfunction with impaired LA-EF≤33% (66% versus 20%, 50% versus 23% and 55% versus 25%, all p<0.05). Conclusions: Left atrial hypertension, electrical conduction slowing and mechanical dysfunction are associated with ACM. These findings improve the understanding of ACM pathophysiology and may be suitable for risk stratification for new-onset AF, arrhythmia recurrence following PVI, and development of novel therapeutic strategies to prevent AF and its associated complications.